Transforming Trauma Teams Through Transactive Memory: Can Simulation Enhance Performance?. (June 2014) - Gardner, Aimee K.; Ahmed, Rami A.
Background: In situ simulation holds promise to enhance the effectiveness of performance. However, a dearth oftheory remains to explain the efficacy ofsimulation-based education within health care teams. Aim: The aim of this study was to examineteam cognitive processes across twotrauma simulations and to identify whether these processes impactobserver-rated performance . Method: Twenty-four health care professionals within anemergency department participated in one of two 30-minute trauma scenarios. Before and after participating, they reported their team transactive memory perceptions. Performance in thescenarios wasvideo recorded for evaluation. Results: Participants reported significantincreases intransactive memory ( p < .05) after participating in the trauma simulations. Furthermore, transactive memory waspositively related to observer-ratedperformance ( r = .58, p < .01). Conclusion: Our results suggest thatsimulation has potential to be an effective method to increasetransactive memory perceptions among team members. In addition, the increase intransactive memory systems is associated withhigher performance ratings. Further consideration concerning thedesign andevaluation of simulation-based training programs to facilitate the development of suchcognitive processes amongteams is recommended.